1993
DOI: 10.1254/jjp.63.399
|View full text |Cite
|
Sign up to set email alerts
|

Effects of OPC-18790, a New Positive Inotropic Agent, on Canine Ventricular Arrhythmias

Abstract: ABSTRACT-OPC-18790is a positive inotropic and vasodilating agent that increases intracellular cyclic AMP and stimulates Ca currents. We examined its direct electrophysiological effects in isolated blood-per fused canine cardiac preparations. OPC-18790 caused an acceleration of the intraventricular conduction in association with an increase of the contractile force and the coronary blood flow. We also examined the effects of OPC-18790 on ventricular arrhythmias in canine ventricular tachycardia (VT) models. OPC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…All these data have led to the search for new therapeutic alternatives for the treatment of heart failure; for example, a study showed that a spiro cycloalkane one induce positive inotropic activity via phosphodiesterase inhibition in an animal model [22]. Other report showed that the compound OPC-18790 is a positive inotropic and vasodilating agent which increases intracellular cyclic AMP and stimulates intracellular Ca +2 currents in an isolated dog heart model [23]. In addition, a study indicated that the compound YS-49…”
Section: Introductionmentioning
confidence: 99%
“…All these data have led to the search for new therapeutic alternatives for the treatment of heart failure; for example, a study showed that a spiro cycloalkane one induce positive inotropic activity via phosphodiesterase inhibition in an animal model [22]. Other report showed that the compound OPC-18790 is a positive inotropic and vasodilating agent which increases intracellular cyclic AMP and stimulates intracellular Ca +2 currents in an isolated dog heart model [23]. In addition, a study indicated that the compound YS-49…”
Section: Introductionmentioning
confidence: 99%